4(3-x)-8=5-(3x-2)

Simple and best practice solution for 4(3-x)-8=5-(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3-x)-8=5-(3x-2) equation:


Simplifying
4(3 + -1x) + -8 = 5 + -1(3x + -2)
(3 * 4 + -1x * 4) + -8 = 5 + -1(3x + -2)
(12 + -4x) + -8 = 5 + -1(3x + -2)

Reorder the terms:
12 + -8 + -4x = 5 + -1(3x + -2)

Combine like terms: 12 + -8 = 4
4 + -4x = 5 + -1(3x + -2)

Reorder the terms:
4 + -4x = 5 + -1(-2 + 3x)
4 + -4x = 5 + (-2 * -1 + 3x * -1)
4 + -4x = 5 + (2 + -3x)

Combine like terms: 5 + 2 = 7
4 + -4x = 7 + -3x

Solving
4 + -4x = 7 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
4 + -4x + 3x = 7 + -3x + 3x

Combine like terms: -4x + 3x = -1x
4 + -1x = 7 + -3x + 3x

Combine like terms: -3x + 3x = 0
4 + -1x = 7 + 0
4 + -1x = 7

Add '-4' to each side of the equation.
4 + -4 + -1x = 7 + -4

Combine like terms: 4 + -4 = 0
0 + -1x = 7 + -4
-1x = 7 + -4

Combine like terms: 7 + -4 = 3
-1x = 3

Divide each side by '-1'.
x = -3

Simplifying
x = -3

See similar equations:

| 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 | | -3+14= | | 4d-6=2(3d-4) | | x^2-14x+196=0 | | -25+25= | | 78=-5x+19 | | 18=-5x+19 | | 33=-5x+19 | | 27=-5x+19 | | 2c+6=0.5(4c+12) | | 6a+5b-2a+-b+7a+3c+a= | | 3(x)+5=8 | | 13=(y+2)-3 | | (x-14)=21 | | 9t-24=57 | | 6x=-4-1 | | 4t-25=9t | | v=.33bh | | w+2=16-6w | | x=120-2x | | x=120-2p | | 4x=3y-7x | | (5x-32)+(3x+28)=180 | | 17/11(5/1)=0 | | 20-2p=3p-10 | | Y=1+1.50x | | 17/11*5/1=7.272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727727272727272727272727272 |

Equations solver categories